Genomic insights into monensin resistance development in Eimeria tenella - Xiaolong Gu; Xiaolong Gu; Sufang Fang; Hongbin Liu; Yubo Shi; Yubo Shi; Yuanyuan Zhang; Peng Wang; Ping Cui; Xinming Tang (Frontiers in Veterinary Science)
IntroductionMonensin resistance in Eimeria tenella poses a significant challenge in poultry farming, compromising the effectiveness of this widely used anticoccidial drug. The present study aimed to identify candidate mutated genes in Eimeria tenella associated with monensin resistance through experimental evolution and pooled genome sequencing.MethodsThe monensin-resistant (MR) strains were rapidly generated by 6 generations of serial passage under gradient monensin treatments using Houghton strain as the parental strain. Genomic sequencing was applied to uncover genetic changes during passages under drug selective pressure. Comparative analysis between resistant and control populations was performed by using the ΔSNP-index and FST values to identify loci with significant selective sweeps. Stringent thresholds were applied to pinpoint candidate genes, followed by annotation and analysis of their potential functions.Results and discussionThe genetic diversity of MR parasites remained stable across generations, despite varying drug concentrations. Seven candidate genes with 11 missense mutations were identified in MR strains. Key genes include ETH2_0729200 (dynein motor protein), ETH2_0729400 (esterase/lipase), and ETH2_0730000 (pyridine nucleotide-disulfide oxidoreductase) annotated in both the selective sweeps by using ΔSNP-index and FST methods. Further experimental validation of these candidate genes is essential to elucidate their roles in monensin resistance. This research contributes valuable insights into the molecular basis of resistance pressure in Eimeria parasites, potentially informing future strategies for the control of coccidiosis.